2017
DOI: 10.1007/s11307-016-1040-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis and Preclinical Evaluation of [18F]F-DPA, A Novel Pyrazolo[1,5a]pyrimidine Acetamide TSPO Radioligand, in Healthy Sprague Dawley Rats

Abstract: PurposeMany neurological conditions result in the overexpression of the translocator protein 18 kDa (TSPO), today recognized as a biomarker for microglial activation and neuroinflammation imaging. The pyrazolo[1,5-a]pyrimidine acetamides are a particularly attractive class of TSPO-specific ligands, prompting the development of several positron emission tomography (PET) radiotracers. This includes F-DPA, a recently reported fluorinated ligand (K i = 1.7 nM), wherein the fluorine atom is directly linked to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 26 publications
(32 reference statements)
1
50
1
Order By: Relevance
“…22 Electrophilic fluorination starting with carrier-added [ 18 F]F 2 to prepare [ 18 F]Selectfluor as a labeling reagent was recently performed by Solin and co-workers, to prepare [ 18 F]2 , and resulted in 15 ± 3% decay corrected yields with a low specific activity of 7.8 ± 0.5 GBq/μmol (0.21 ± 0.01 Ci/μmol). 23 However, because a low-cold-mass PET ligand injection is critical to detect inflammatory events, 24, 25 there is an unmet and urgent need for [ 18 F]2 with high specific activity to evaluate the potential of this radioligand in PET imaging of neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Electrophilic fluorination starting with carrier-added [ 18 F]F 2 to prepare [ 18 F]Selectfluor as a labeling reagent was recently performed by Solin and co-workers, to prepare [ 18 F]2 , and resulted in 15 ± 3% decay corrected yields with a low specific activity of 7.8 ± 0.5 GBq/μmol (0.21 ± 0.01 Ci/μmol). 23 However, because a low-cold-mass PET ligand injection is critical to detect inflammatory events, 24, 25 there is an unmet and urgent need for [ 18 F]2 with high specific activity to evaluate the potential of this radioligand in PET imaging of neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Keller et al compared the activity of 38 with its analogue [ 18 F]F-DPA (39) (Figure 15), which presents the radionuclide directly linked to the phenyl ring. This study showed that compound 39 is metabolically more stable than its analogue 38 in rats' brains, being regarded as a promising TSPO radiotracer, because it shows a higher ratio between specific and nonspecific binding [81]. Later, in 2018, the same author described the potential of [ 18 F]F-DPA 39 to visualize activated microglia at an early stage of AD pathology.…”
Section: Translocator Protein Receptor Ligandsmentioning
confidence: 92%
“…24 Electrophilic fluorination with [ 18 F]Selectfluor as a labeling reagent was also performed to prepare [ 18 F]FDPA. Although the obtained radioactivity by this method was applied for rodent PET imaging, 22,23 the complicated labeling procedure 27 as well as the low molar specific activities of ca. 7.7 GBq/μmol (0.2 Ci/μmol) 22,23,[25][26][27] would be challenging for further translational research.…”
Section: Automated Synthesis Of [ 18 F]fdpamentioning
confidence: 99%
“…18 19 [ 18 F]FDPA, an analog of [ 18 F]DPA-714, showed excellent binding affinity for TSPO (Ki = 2.0 ± 0.8 nM using the same [ 3 H]PK11195 binding assay and positive controls described in the DPA-714 work), 11 excellent selectivity toward central benzodiazepine receptor (Ki > 1 mM), and reasonable lipophilicity (LogD = 2.34) for crossing blood-brain barrier. 20,21 More importantly, its aryl-18 F bond significantly reduced the potential generation of radiolabeled metabolites in the brain and plasma, 22 which would help PET quantification. Solin 22,23 and our group 21 have conducted PET imaging studies on APP/PS1 transgenic mouse model.…”
mentioning
confidence: 99%
See 1 more Smart Citation